Psychosocial Problems among the Adolescent School Students of Dhulikhel Municipality - Shrestha, B.; Gautam, S.; Shrestha, J.; Shrestha, S. (Kathmandu University Medical Journal, 2021)
Background Adolescence is a period when an individual experiences a variety of biological, psychological and social changes. These multiple changes during the developmental period can make the adolescents vulnerable to mental health problems. Therefore early detection of psychosocial problems and addressing the need of the adolescents are crucial for promoting their mental health. Objective To assess psychosocial problems and its associated factors among school going adolescents of Dhulikhel, Nepal. Method A descriptive cross sectional study was conducted among 513 adolescents studying in grade 8 to 12 of randomly selected schools of Dhulikhel Municipality. Data were collected by using structured questionnaire and Pediatric Symptom Checklist-Youth Report (Y-PSC). Descriptive and inferential analysis was done using Statistical Package for Social Sciences version 20. Result Out of 513 adolescent students, a total of 133(25.9%) of the adolescents were found to have psychosocial problems. There was significant association between psychosocial problems and respondents’ variables like age, grade, parental education status, respondents’ living status, perceived family disputes, perceived marital problems of parents, relationship problem with family, stress of failure in study, punishment faced in home and school, experienced sexual harassment and death of loved ones. Conclusion Various family related factors and stressful life events of adolescents are associated with the psychosocial problems. Hence early intervention focusing on awareness and modification of stressful life events is required.